Kepemimpinan Pendidikan Multikultural (Tantangan dan Solusinya) - Syam Sudin (LP2M Sekolah Tinggi Agama Islam Nahdlatul Ulama Pacitan, 2017)
Indonesian with a very wide area that consists of thousands of ethnic groups, languages, religions, traditions and cultures also interact and mingle to form a multi-ethnic society. The migration of Arabs, China, and India to the Indonesian archipelago increased the diversity of the nation. Indonesian multiculturalism has the potential that can be developed to improve welfare. However, these conditions also potential to conflicts among ethnic groups, religious, and cultures. Horizontal conflicts that occurred in Sambas, Poso, Sampit, Tasikmalaya, and others show that multiculturalism needs to be managed so it gives positive impact on the progress and welfare of the community. In the Indonesian context, the awareness of multiculturalism needs to inculcated in the life of the nation and society. There are recognition and inter-ethnic tolerance that led to the establishment of cooperation and trust so as to create a peaceful and democratic life. As a multicultural country, Indonesia should have the awareness of multiculturalism that tribes who settle in the region establish interaction and communication between the healthy and dynamic society in order to create a democratic, harmonious, and peaceful community. Education is the starting point for reconstruction of multicultural culture in a democratic society. Through school teachers can instill pluralistic nature and practice into learners. Teachers need to be creative in bridging cultural plurality and a pluralistic and peaceful community. As the spearhead of multicultural education, teachers must have an adequate understanding of multiculturalism and multicultural education. In the teaching activities, teachers develop multiculture-oriented climate that highlights social justice and culture.